Pain and Health-Related Quality of Life After Oral Soft Tissue Surgical Intervention: The Advantages of the Nd:YAG Laser - Giovannacci, Ilaria; Vescovi, Paolo; Mergoni, Giovanni; Fornaini, Carlo; Bonanini, Mauro; Meleti, Marco (UI Scholars Hub, 2014)
The new technology such as the neodymium-doped yttrium aluminum garnet (Nd:YAG) laser has been used for oral soft tissue surgery. Previous study shown that laser surgery resulted in lower morbidity and complication rates. Objective: This study aims to evaluate the differences in the post-operative course associated to the use of Nd:YAG laser and to cold blade after oral soft tissue surgery. Methods: One-hundred and eighteen comparable surgical interventions were evaluated. Group 1 (G1) included 77 interventions performed with Nd:YAG laser; group 2 (G2) 41 with cold blade. Acute post-operative pain was evaluated with visual analogue scale (VAS), numeric rating scale (NRS) and verbal rating scale-6 (VRS-6) on the same day of surgery, and at 1, 3 and 7 days after surgery.The HRQoL was evaluated on day 7 using a 0-45 score range questionnaire. Data were analyzed using the software STATA 12 (StataCorp LP, College Station, Texas, USA). Results: No statistically significant differences could be highlighted in VAS and NRS scores. The VRS-6 scores resulted statistically significant at days 1 and 3. At day 1, 47.14% of patients in G1 and 13.16% in G2 had no pain; at day 3, 62.86% in G1 and 21.05% in G2 had no pain. The HRQoL in G1 was statistically higher than G2. Conclusion: The better HRQoL and the lower post-operative pain observed in laser-treated patients may be associated to the possible bio-modulating effect of the laser.